Academic Career Development of Chinese Returnees With Overseas Ph.D. Degrees: A Bioecological Development Perspective - Liu, Dan; Xu, Yuwei; Zhao, Tongtong; Che, Siqi (Frontiers in Psychology, 2022)
This study uses the bioecological model of human development to understand the academic career development of Chinese returnees with overseas PhD degrees (CROPs). Focuses are placed on how CROPs engaged in this process through interactions with contexts, which lead to their differentiated and similar career development in Chinese higher education. Using a qualitative approach of semi-structured interviews with 31 CROPs, our findings reveal that CROPs’ academic career development is co-shaped by personal characteristics and multi-layered environmental contexts. The study highlights the dysfunctionality of Chinese higher education system in the context of China’s ambition to build First-class Universities and First-class Subjects (Double First-class), which constrains CROPs’ academic career development. The paper offers important implications for potential CROPs, policy, and future research studies.